Momentum and disposition effect in the US stock market - Ranjeeta Sadhwani (Taylor & Francis Group, 2021)
This paper examines whether momentum drives the disposition effect and vice versa in the US stock market. The results from the analysis of the Fama-Macbethregressions show that the disposition effect drives momentum but not the other way around. Furthermore, we find that this relationship varies over time. Along with the disposition effect, size also has an impact on the momentum. Therefore, the relationship between momentum and disposition effect is examined based on size deciles, and results demonstrate that the relationship does not vary significantly with the size of stocks. However, both the cumulative returns and capital gain varies monotonically with the size of stocks.